NEUROPATHY, ATAXIA, AND RETINITIS PIGMENTOSA SYNDROME: A MULTIDISCIPLINARY DIAGNOSIS. Issue Volume 15:Issues 4(2021) (July 2021) - Juaristi, Leire; Irigoyen, Cristina; Quiroga, Jorge
Abstract : Purpose: To report a case of neuropathy, ataxia, and retinitis pigmentosa syndrome, a rare and undiagnosed disease in ophthalmology due to the need for multidisciplinary evaluation. Methods: Multimodal testing was performed, including neurologic, ophthalmologic, and genetic assessments. The neurologic tests comprised electromyogram and muscle biopsy; the ophthalmologic examination consisted of slit-lamp and fundus examinations, optical coherence tomography, visual field testing, and electrophysiology tests such as a full-field electroretinogram and multifocal electroretinogram; and genetic tests were performed for spinocerebellar ataxia. In addition, the patient underwent magnetic resonance imaging, an electrocardiogram, cerebrospinal fluid analysis with lactate levels, and a blood workup including antineuronal, antithyroid peroxidase, antinuclear, antimitochondrial, and antitransglutaminase antibodies and fat-soluble vitamins (A, D, E, K). Results: The ocular fundus examination showed bone spicules with retinal pigment epithelium alteration, optic nerve pallor, and arterial attenuation. Optical coherence tomography demonstrated macular atrophy. Visual field testing revealed concentric reduction. Electrophysiology examinations showed involvement of rods and cones in both eyes. The muscle biopsy was compatible with mitochondrial disease, and electromyogram demonstrated sensory axonal damage. However, genetic tests for spinocerebellar ataxia were negative. Magnetic resonance imaging showed cerebellar atrophy, whereas the electrocardiogram did not detect any abnormalities. Cerebrospinal fluid lactate levels were above normal but antibody levels in blood were normal. Conclusion: This is the first report of macular atrophy demonstrated by optical coherence tomography in a patient with neuropathy, ataxia, and retinitis pigmentosa syndrome. For the diagnosis, a multidisciplinary team including a neurologist, a geneticist, and an ophthalmologist was essential. Patients with suspected mitochondrial disease could greatly benefit from an ophthalmology examination like that conducted in this case because it was the key factor that led to the suspicion of syndromic disease, and ultimately the diagnosis. Abstract : Neuropathy, ataxia, and retinitis pigmentosa syndrome, an infrequent and underdiagnosed disease in ophthalmology due to the need for multidisciplinary evaluation. Patients with suspected mitochondrial disease could greatly benefit from an ophthalmology examination.